Introduction to computable general equilibrium models - Burfisher, Mary E. (Cambridge : Cambridge University Press, 2021)
Computable general equilibrium (CGE) models play an important role in supporting public-policy making on such issues as trade, climate change and taxation. This significantly revised volume, keeping pace with the next-generation standard CGE model, is the only undergraduate-level introduction of its kind. The volume utilizes a graphical approach to explain the economic theory underlying a CGE model, and provides results from simple, small-scale CGE models to illustrate the links between theory and model outcomes. Its eleven hands-on exercises introduce modelling techniques that are applied to real-world economic problems. Students learn how to integrate their separate fields of economic study into a comprehensive, general equilibrium perspective as they develop their skills as producers or consumers of CGE-based analysis.
Title from publisher's bibliographic system (viewed on 14 Dec 2020).
Keywords: Computable general equilibrium models; Equilibrium (Economics) -- Mathematical models